Development and clinical validation of a non-invasive, beat-to-beat blood pressure monitoring device, compared to invasive blood pressure monitoring during coronary angiography - Borges,Melania Aparecida (2019)
ABSTRACT Objective To develop and test a beat-to-beat blood pressure monitoring device during coronary angiography, and compare it with invasive blood pressure monitoring. Methods Twenty-eight patients with an indication for hemodynamic study were selected for this investigation, and kept in supine position. Before starting the coronary angiography, they were instructed about the use of the left radial bracelet for beat-to-beat blood pressure monitoring. Results There was a significant difference between the time required for the catheterization laboratory team to acquire the first invasive blood pressure reading and the time to obtain the first beat-to-beat reading (11.1±5.1 and 1.5±1.8, respectively; p<0.0001). The intraclass correlation coefficients (95%CI) of systolic and diastolic blood pressures were 0.897 (0.780-0.952) and 0.876 (0.734-0.942), indicating good reproducibility. Conclusion This study showed the process to develop a beat-to-beat blood pressure monitoring device. When compared to invasive blood pressure monitoring, there were no significant differences between the two methods. This technique may play a promising coadjuvant role when combined with invasive monitoring during coronary angiography procedures.